2024
DOI: 10.1186/s12902-024-01564-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between insulin resistance and the rate of neutrophils-lymphocytes, monocytes-lymphocytes, platelets-lymphocytes in type 2 diabetic patients

Yuanyuan Zhang,
Huaizhen Liu

Abstract: Background Insulin resistance (IR) was a prominent feature commonly observed in individuals with type 2 diabetes mellitus (T2DM). T2DM Individuals often exhibited a concomitant presence of low-grade chronic inflammation. In this study conducted retrospectively, the aim was to investigate the connection between neutrophils-lymphocytes rate (NLR), monocytes-lymphocytes rate (MLR), platelets-lymphocytes rate (PLR) and IR, specifically among individuals with T2DM. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In a systematic meta-analysis study examining the changes in hematologic parameters of patients with type 2 DM and type 1 DM and a control group of healthy individuals, it was shown that patients with type 2 DM had significantly higher absolute neutrophil, absolute monocyte, absolute lymphocyte, and absolute basophil counts and relative neutrophil and basophil counts [ 23 ]. In addition, another study reported that hematologic parameters, such as the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-platelet ratio, were higher in patients with diabetes and that these increases could be considered a sign of inflammatory response [ 24 ]. In another study, the neutrophil levels of patients with type 2 DM and healthy individuals were compared, and it was found that the neutrophil levels of the patient group were significantly higher [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic meta-analysis study examining the changes in hematologic parameters of patients with type 2 DM and type 1 DM and a control group of healthy individuals, it was shown that patients with type 2 DM had significantly higher absolute neutrophil, absolute monocyte, absolute lymphocyte, and absolute basophil counts and relative neutrophil and basophil counts [ 23 ]. In addition, another study reported that hematologic parameters, such as the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-platelet ratio, were higher in patients with diabetes and that these increases could be considered a sign of inflammatory response [ 24 ]. In another study, the neutrophil levels of patients with type 2 DM and healthy individuals were compared, and it was found that the neutrophil levels of the patient group were significantly higher [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Type 2 diabetes mellitus (T2DM) is mainly characterized by increased chronic inflammation burden. 5 , 6 In addition, diabetic microvascular complications including diabetic peripheral neuropathy (DPN) are also characterized by a high inflammatory burden. 7 , 8 It is widely believed that DPN is a devastating complication of DM characterized by complex molecular pathogenesis.…”
Section: Introductionmentioning
confidence: 99%